microRNAs in uterine sarcomas and mixed epithelial–mesenchymal uterine tumors: a preliminary report - Kowalewska, Magdalena (Springer Netherlands, 2013)
Uterine sarcomas and mixed epithelial–mesenchymal uterine tumors are a heterogeneous group of rare tumors for which there are very few diagnostic markers available. As aberrant microRNA (miRNA) expression patterns represent putative diagnostic cancer markers, we aimed to identify miRNA expression profiles of the major uterine sarcoma subtypes and mixed epithelial–mesenchymal tumors of the uterus. Eighty-eight miRNAs were assessed by quantitative RT-PCR in cancerous and non-cancerous tissue samples collected from 29 patients with endometrial sarcoma, leiomyosarcoma, and mixed epithelial–mesenchymal tumors. Tumor and control samples significantly (P < 0.05) differed in the expression of miR-23b, miR-1, let-7f, and let-7c in endometrial sarcomas, and miR-1, let-7c, miR-133b, let-7b, miR-143, let-7a, let-7d, let-7e, let-7g, miR-222, let-7i, and miR-214 in mixed epithelial–mesenchymal tumors. All the significantly changed miRNAs were down-regulated in the malignant tissues as compared to their normal counterparts. This may suggest their tumor suppressor role in these malignancies. No statistically significant changes in miRNA expression levels were found between leiomyosarcoma tumors and controls. The identified miRNAs warrant further studies as valuable candidate markers for the differential diagnosis of uterine sarcomas from benign uterine lesions and between uterine sarcoma subtypes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13277-013-0748-5) contains supplementary material, which is available to authorized users.